Transfer and Religion: Interactions between Judaism, Christianity and Islam from the Middle Ages to the Twentieth Century - Dubrau, Alexander A.; Scotto, Davide; Vimercati Sanseverino, Ruggero (Sapientia Islamica, 2020)
Der vorliegende Band vereinigt Beiträge aus den jüdischen und islamischen Studien, der christlichen Theologie sowie der Kulturwissenschaft, welche die anhaltenden theologischen und kulturellen Interaktionen zwischen den abrahamitischen Glaubensrichtungen im Mittelmeerraum und Mitteleuropa seit dem Mittelalter beleuchten. Das Buch präsentiert Fallstudien der facettenreichen Wechselwirkungen zwischen Judentum, Christentum und Islam aus historischer und theologischer Perspektive. Der vorliegende Sammelband diskutiert die intellektuelle Fruchtbarkeit religiöser Transformationen und trägt dazu bei, die konstruktive Herausforderung religiöser Konzepte, Glaubenslehren und Narrationen zu bestimmen, die sich aus den Interaktionen zwischen Judentum, Christentum und Islam ergeben.InhaltsübersichtFrom Polemical Purposes to Intercultural Mediation. The Making of Religious Transfer in the Middle Ages and Early-Modern Times Daniel Boušek: Entangled Arguments. A Survey of Religious Polemics Between Islam and Judaism in the Middle Ages – Tzvi Langermann: Moses Maimonides (1135–1204) and al-Qāḍī al-Fāḍil (1135–1200), his Friend and Patron. Between Islam and Judaism – Nadjet Zouggar: Aspects de la polémique antiphilosophique de Taqī al-Dīn Aḥmad Ibn Taymiyya (m. 728/1328). La critique d'un transfert – Ana Echevarría Arsuaga: Neue Moscheen in christlichen Ländern. Die Debatte im Mittelalter – Davide Scotto: Translation in Wartime. Disseminating the Qur'ān during the Crusades (Twelfth to Fifteenth Centuries) – Irina Synkova and Michail Tarelka: 'Whence the Idols Have Arrived'. The Monument of the Religious-Polemic Literature from the Tatars Manuscript Heritage of the Former Grand Duchy of Lithuania – Andrea Celli: The Early-Modern Invention of »Abrahamic Religions«. An Overview of Baroque Approaches to the Hagar Narrative Models of Knowledge and the Secularisation of Inter-Faith Coexistence. Implications of Religious Transfer in the Modernity Ottfried Fraisse: Modernisierung des Judentums durch Wissenschaft und der Rekurs auf den Islam. Moritz Steinschneider, Ignác Goldziher, Shlomo Pines – Enas Aly Ahmed: From Polemical Discourse to Cultural Transmission in Spanish Arabism and European Orientalism. The Case of Miguel Asín Palacios's Study of al-Fiṣal by Ibn Ḥazm – Alexander A. Dubrau: A Jewish Orthodox Response to the Hostility towards the Morality of Jewish Law and the Jewish God at the Turn of the Twentieth Century in Germany. Rabbi David Zvi Hoffmann (1843–1921) on the Relationship between Jews and Gentiles – Alon Segev: Religion, Race and Politics. Gerhard Kittel and the Jewish Question – Ulli Roth: Das Konzil und der christliche Blick auf den Islam. Gemeinsame Impulse des Basler Konzils und des II. Vaticanums – Ruggero Vimercati Sanseverino: Conflicting Images of Muhammad and Secularization in Contemporary Islam. The Critical Meaning of Prophetology According to ʿAbd al-Ḥalīm Maḥmūd (1910–1978)